Views of primary care providers regarding the return of genome sequencing incidental findings. (20th May 2014) - Strong, K.A.; Zusevics, K.L.; Bick, D.; Veith, R.
Abstract Sequencing of the entire exome or genome is increasingly used in clinical practice. Debate continues, however, regarding which incidental findings (IFs) should be returned and who should be involved in those decisions. Previous empirical research regarding stakeholder attitudes to the return of IFs has primarily involved genetics professionals; non‐genetics health professionals have not been widely surveyed. Given this, a survey regarding return of IFs was administered at the Best Practices in Pediatrics Conference following an educational presentation on genetics terminology and genetic condition examples. A total of 258 participants completed the survey. Of particular note, respondents who were positively disposed to sequencing did not always report wanting to learn about IFs, even if actionable. This is noteworthy given recent American College of Medical Genetics and Genomics guidelines recommending particular actionable IF be returned 'without reference to patient preference'. This study's findings are important because they provide insight regarding the attitudes to the return of genome sequencing results for an important professional group, primary care providers. Ultimately, as likely gatekeepers to referrals for this technology, their opinions about the test will be key to its successful deployment.